Accessible light-controlled knockdown of cell-free protein synthesis using phosphorothioate-caged antisense oligonucleotides - Denis Hartmann; Michael J. Booth (Communications Chemistry, 2023)
Light-activated antisense oligonucleotides have been developed to induce gene knockdown in living cells, however, their synthesis remains challenging and application in cell-free systems is underexplored. Here, the authors report a one-step method for selectively attaching photocages onto phosphorothioate linkages of antisense oligonucleotides that can knockdown cell-free protein synthesis using light.